Pembelajaran Bahasa Inggris Untuk Anak-Anak di Daerah Pesisir Pantai SDN Pulo Panjang I Kecamatan Pulo Ampel Kabupaten Serang - Prihartini, Ade Rahayu; Maesaroh, Maesaroh; Imam Alfarizi, Muhammad; Melisa, Melisa; Ayu Refina Oktaviani, Mas (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2025)
English plays a vital role for school children, both for their personal development, academics, and the future of the nation. English is considered a universal language because it is widely used in various countries as a primary language. Furthermore, it is also an international language that is crucial to master or learn. English learning should begin at preschool age, as this is the stage at which children most easily absorb and develop their language skills. Early learning also has a positive impact on English mastery as they progress through elementary school and college. Therefore, the goal of these English learning activities is expected to increase motivation to learn English and contribute to academic achievement at school.